2016
DOI: 10.1108/lm-09-2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Contributing factors in knowledge sharing for performance of university students in teachers’ training programs

Abstract: Purpose The purpose of this paper is to study stated effects of independent variables of trust, social networks, and information and communication technologies (ICTs) on explicit and tacit knowledge. Further, it explained contributions of explicit and tacit knowledge to performance in academic environment. Design/methodology/approach This study is based on research model of hypothetical relationships of various criterion and predictor variables. Structural equation model was used in which research model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
6
7
1
Order By: Relevance
“…The results also show that knowledge sharing relates to team performance in VLE, a finding which is consistent with those of existent studies [34,48]. In our study, explicit knowledge sharing was found to be positively associated with team performance not only directly but also via tacit knowledge sharing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results also show that knowledge sharing relates to team performance in VLE, a finding which is consistent with those of existent studies [34,48]. In our study, explicit knowledge sharing was found to be positively associated with team performance not only directly but also via tacit knowledge sharing.…”
Section: Discussionsupporting
confidence: 93%
“…On the one hand, these results corroborate that explicit knowledge sharing contributes to team learning performance in VLE, which supports our H6. On the other hand, the mediating effect of tacit knowledge sharing recalls the results of Elton [13], Shah and Mahmood [34], and Zaqout and Abbas [48], which illustrated that tacit knowledge and explicit knowledge are both better for academic research. Regarding our research results, meaningful implications in both theoretical and practical terms are discussed next.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Table 4, 5 and 10 sustain this proposition where a high proportion of student teachers expressed their unreadiness to integrate ICTs into their teaching practice because of the lack of proper ICTs' training. These findings echo results emerged from many researches mentioned earlier, that student teachers need to be provided with sufficient ICTs training in order to increase their readiness to implement efficiently ICTs into their future education (Enochsson, 2010;Janssens-Bevernage et al, 2010;Shah & Mahmood, 2016). Therefore, in Table 7 and 8 we witnessed a consensus among student teachers that free access to university computer laps and training courses are crucial to the enhancement ICTs skills.…”
Section: Discussionsupporting
confidence: 69%
“…The results indicated that KBT significantly predicted WSTK. However, KBT contradicts Shah and Mahmood's (2016) findings that trust is not significant within a tacit knowledge-sharing relationship. Conversely, KBT supported Endres and Rhoad's (2016) finding that repeat interactions promote tacit knowledge transfer.…”
Section: Theoretical Implicationscontrasting
confidence: 61%